2020
DOI: 10.1111/phn.12799
|View full text |Cite
|
Sign up to set email alerts
|

“You got to eat, but then what you are eating, it’s going to kill you”: Living with hypertension while experiencing homelessness

Abstract: Heart disease, including hypertension, is a leading cause of morbidity and mortality among persons experiencing homelessness (PEH). PEH exhibit a greater number of modifiable risk factors for hypertension than the general population and are challenged to reach optimal blood pressure control despite receiving medical treatment. This descriptive qualitative study used data collected from three focus groups to explore the barriers and facilitators of self‐management of hypertension while experiencing homelessness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Seven themes from five different studies reported that participants had a sense of healthy eating, however, they were unable to follow through on a healthy food regimen given that they were focused on eating for basic survival (Groton et al, 2021; Paudyal et al, 2020; Persaud et al, 2010; Sprake et al, 2014; Wicks et al, 2006). Some described going to creative lengths to eat healthier options, such as cooking out of a van or attending multiple meal programs (Groton et al, 2021), while others noted poor dental conditions limited their ability to chew healthy foods provided (Wicks et al, 2006). Participants had a keen desire for healthy food (Sprake et al, 2014; Wicks et al, 2006), however, this often could not be prioritised.…”
Section: Resultsmentioning
confidence: 99%
“…Seven themes from five different studies reported that participants had a sense of healthy eating, however, they were unable to follow through on a healthy food regimen given that they were focused on eating for basic survival (Groton et al, 2021; Paudyal et al, 2020; Persaud et al, 2010; Sprake et al, 2014; Wicks et al, 2006). Some described going to creative lengths to eat healthier options, such as cooking out of a van or attending multiple meal programs (Groton et al, 2021), while others noted poor dental conditions limited their ability to chew healthy foods provided (Wicks et al, 2006). Participants had a keen desire for healthy food (Sprake et al, 2014; Wicks et al, 2006), however, this often could not be prioritised.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies with individuals experiencing homelessness have identified a good awareness of healthy behaviours and experience of similar barriers including: the type and availability of food and preparation facilities; access to exercise; and limited opportunities for stress reduction 17 22. Smoking cessation has been described as something to address after other priorities were resolved17—with social acceptability and pressure, behind preferences to reduce, rather than stop, smoking 23.…”
Section: Discussionmentioning
confidence: 99%
“…While a number of studies have focused on the link between access to hygiene facilities and disease risk in the homeless population, 24 25 fewer have focused on the potential psychological impacts. 26 Inability to access water, sanitation and hygiene facilities causes stress and acts as a barrier not only to exercise, 22 but to other higher-level needs such as securing employment 27 ; and can be viewed as an important aspect of health itself in those experiencing homelessness. 17 Stigma and shame arising from lack of access to hygiene has also been described as a key feature in reluctance to access health services 17 28 ; with experiences being described as shaped by 'discrimination, disrespect and disempowerment'.…”
Section: What Is Already Knownmentioning
confidence: 99%
“…Previous studies with individuals experiencing homelessness have identified a good awareness of healthy behaviours and experience of similar barriers including: the type and availability of food and preparation facilities; access to exercise; and limited opportunities for stress reduction [17,22]. Smoking cessation has been described as something to address after their other priorities were resolved [17] – with social acceptability and pressure, behind preferences to reduce, rather than stop, smoking [23].…”
Section: Discussionmentioning
confidence: 99%
“…While a number of studies have focussed on the link between access to hygiene facilities and disease risk in the homeless population [24,25], fewer have focussed on the potential psychological impacts [26]. Inability to access water, sanitation and hygiene facilities causes stress and acts as a barrier not only to exercise [22], but to other higher-level needs such as securing employment [27]; and can be viewed as an important aspect of health itself in those experiencing homelessness [17].…”
Section: Discussionmentioning
confidence: 99%